2020
DOI: 10.1049/iet-rpg.2019.0941
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven weather forecasting models performance comparison for improving offshore wind turbine availability and maintenance

Abstract: Wind energy is an attractive alternative to conventional sources of electricity generation due to its effectively zero carbon emissions. Wind power is highly dependent on wind speed and operations offshore are affected by wave height; these together called turbine weather datasets that are variable and intermittent over various timescales and signify offshore weather conditions. In contrast to onshore wind, offshore wind requires improved forecasting since unfavourable weather prevents repair and maintenance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…[ 240 ] The wind power prediction for maintenance planning is crucial for backup power systems, exploration after severe climate circumstances, smooth weather prediction during the process, and selection of suitable control system architecture. [ 241,242 ]…”
Section: Process Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 240 ] The wind power prediction for maintenance planning is crucial for backup power systems, exploration after severe climate circumstances, smooth weather prediction during the process, and selection of suitable control system architecture. [ 241,242 ]…”
Section: Process Applicationsmentioning
confidence: 99%
“…[240] The wind power prediction for maintenance planning is crucial for backup power systems, exploration after severe climate circumstances, smooth weather prediction during the process, and selection of suitable control system architecture. [241,242] The sitting of a wind farm is a crucial factor affecting the generated power by wind turbines. [243] Evaluations regarding the area's energy potential where the wind farm will be established are significant to ensure maximum efficiency from the installed plant.…”
Section: Technical Planningmentioning
confidence: 99%
“…Various techniques to forecast wind speed and wave height have been proposed, including data-driven and physical models. Pandit et al (2020) proposed a data-driven model for weather forecasting in offshore environments and found that more accurate weather forecasts can decrease O&M costs by up to 3%. As presented in Fig.…”
Section: Cost Objectivementioning
confidence: 99%
“…The chaining of customisable cells makes the LSTM model especially useful for working with data that include cyclical events over long time intervals, such as climate data sets. Moreover, LSTM models work well even with long delays between significant events in the input data and are also suitable for long‐term forecasting [43].…”
Section: Forecast Modelsmentioning
confidence: 99%